RDT- AND MICROSCOPIC-BASED TRENDS OF MALARIA AMONG LOCAL AND MIGRANT POPULATIONS IN THE PROVINCE OF CENTRAL KALIMANTAN, INDONESIA DURING 2017-2020: Trend of malaria among local and migrant population - ARWATI, Heny; LESTARISA, Trilianty; AUGUSTINA, Indria; ROHMAH, Etik Ainun; SUBEKTI, Sri; KEMAN, Soedjajadi; DACHLAN, Yoes Prijatna (African Journal of Infectious Diseases (AJID), 2022)
Background: Indonesia has demonstrated a significant progress in malaria elimination. Kapuas and Gunung Mas Districts in Central Kalimantan Province have not been freed from malaria and there is no information of malaria incidences in these areas. Palangka Raya city has been freed from malaria in 2018. Materials and Methods: The total number of 140 samples consisting of 75 malaria Giemsa-stained blood smears and 65 RDT cartridges from both local and migrant populations. Both males and females aged 15 years and above were included and their demographic data were recorded. The malaria trend in these areas was analyzed based on the number of cases, species of Plasmodium and the demographic characteristics of the enrolled subjects. Results: The study findings disclosed a yearly decrement of malaria trend in both local and migrant populations of the studied areas. The highest number of P. vivax infection (8.76%) occurred in 2018 among migrant population in Gunung Mas district, while P.falciparum infection was found in 2017 contributed by both population. The decreased number of cases was shown by very low number of cases during 2019 and 2020. The observed significant decrease in malaria incidences indicated the implementation of the malaria control programs at the sub-district level. Conclusion: To minimize malaria cases among gold miners, mosquito repellent, prophylactic administration of antimalarial drugs and enough enlightenment should be considered before and during their activities. From that standpoint, the effective collaboration between health officers and environmental authorities is recommended to control, prevent and eradicate malaria in these areas.